(3eSDhdjI GdfGbd GdHMQjs (3habG GdGJaGbjI GdGee GdeJMOI dfbd GdHVGFY HGdHMQs - (3jMj(B, (3SYjOs ((3GdGScfOQjIs (3GdecJH GdYQHj GdMOjKs, 2000)
(3JMdjd GdGMcGe GdNGUI HfhYjI Gdfbd eLGd GdeSDdjI ,GdGMcGe GdNGUI HfWGb JWHjb GdGJaGbjI , GdGMcGe GdNGUI HeOI GdeSDdjI GdGMcGe GdNGUI HCSGS GdeSDdjI , JMdjd GdGMcGe GdNGUI HJMOjO GdeSDhdjI JMdjd HYU GdMGdGJ aj eSDdjI GdfGbd GdGMcGe GdNGUI HGdGNWGQGJ , GdGMcGe GdNGUI HJbGOe GdOYGhi , GdGMcGe GdNGUI HGdGNJUGU , GdGMcGe GdNGUI HGdJMcjes
Keywords: (3GdEJaGbjGJ GdOhdjIs; (3GdSdYs; (3GdbGfhf GdHMQjs; (3Gdfbd GdHMQjs